🎉 从330转为WashU帮助手册啦!

Math429
模块
Math429 L27

Lecture 27

Chapter VI Inner Product Spaces

Orthonormal basis 6B

Theorem 6.32 Gram-Schmidt

Suppose v1,...,vmv_1,...,v_m is a linearly independent list. Let fkVf_k\in V by f1=v1f_1=v_1, and fk=vkj=1k1vk,fjfj2fjf_k=v_k-\sum_{j=1}^{k-1}\frac{\langle v_k,f_j\rangle }{||f_j||^2}f_j. Then set ek=fkfke_k=\frac{f_k}{||f_k||}, then e1,...,eme_1,...,e_m is orthonormal with Span(e1,...,ek)=Span(v1,...,vk)Span(e_1,...,e_k)=Span(v_1,...,v_k) for each k=1,...,mk=1,...,m

Proof: note is suffice to show that f1,...,fmf_1,...,f_m is orthogonal and that Span(e1,...,em)=Span(v1,...,vm)Span(e_1,...,e_m)=Span(v_1,...,v_m) Induct on mm.

When m=1m=1: clear

When m>1m>1: Suppose we know the result for values <m< m. Need to show that fm,fk=0\langle f_m,f_k\rangle =0 for k<mk<m.

fm,fk=vm,fkj=1k1vm,fjfj2fj,fk=vm,fkvm,fkfj2fk,fk=vm,fkvm,fk=0\begin{aligned} \langle f_m, f_k \rangle &=\langle v_m, f_k \rangle-\sum_{j=1}^{k-1}\frac{\langle v_m,f_j\rangle }{||f_j||^2} \langle f_j, f_k \rangle\\ &=\langle v_m, f_k \rangle-\frac{\langle v_m,f_k \rangle }{||f_j||^2} \langle f_k, f_k \rangle\\ &=\langle v_m, f_k \rangle-\langle v_m,f_k \rangle\\ &=0 \end{aligned}

Then we want to test if Span(f1,...,fm)=Span(v1,...,vm)Span(f_1,...,f_m)=Span(v_1,...,v_m), given that Span(f1,...,fm1)=Span(v1,...,vm1)Span(f_1,...,f_{m-1})=Span(v_1,...,v_{m-1}) (by induction)

Since fm=vmj=1m1vm,fjfj2fjf_m=v_m-\sum_{j=1}^{m-1}\frac{\langle v_m,f_j\rangle }{||f_j||^2}f_j, and j=1m1vm,fjfj2fjSpan(v1,...,vm1)\sum_{j=1}^{m-1}\frac{\langle v_m,f_j\rangle }{||f_j||^2}f_j \in Span(v_1,...,v_{m-1}), then fmSpan(v1,...,vm)f_m\in Span(v_1,...,v_m)

Since vm=fmj=1m1vm,fjfj2fjSpan(f1,...,fm)v_m=f_m-\sum_{j=1}^{m-1}\frac{\langle v_m,f_j\rangle }{||f_j||^2}f_j \in Span(f_1,...,f_m), then vmSpan(f1,...,fm)v_m\in Span(f_1,...,f_m)

Example: Find an orthonormal basis for P2(R)\mathscr{P}_2(\mathbb{R}) with p,q=11pq\langle p,q \rangle=\int^1_{-1}pq.

Start with 1,x,x21,x,x^2, apply Gram-Schimidt procedure.

f1=1f_1=1,

f2=xx,1121=x021=xf_2=x-\frac{\langle x,1 \rangle}{||1||^2}1=x-\frac{0}{2}\cdot 1 =x,

f3=x3x2,1121x2,x12x=x22/321=x213f_3=x^3-\frac{\langle x^2,1 \rangle}{||1||^2}1-\frac{\langle x^2,x \rangle}{||1||^2}x=x^2-\frac{2/3}{2}1=x^2-\frac{1}{3}

Convert it to orthonormal basis we have 12,32x,458(x213)\sqrt{\frac{1}{2}}, \sqrt{\frac{3}{2}}x,\sqrt{\frac{45}{8}}(x^2-\frac{1}{3})

Theorem 6.35

Every finite dimensional inner product space has an orthonormal basis

Proof:

take any basis and apply Gram-Schmidt procedure.

Theorem 6.36

Every orthonormal list extends to an orthonormal basis.

Proof:

extend the basis and apply Gram-Schmidt procedure.

Theorem 6.37

VV be a finite dimensional TL(V)T\in \mathscr{L}(V). Then TT has an upper triangular matrix with respect to an orthonormal basis     \iff if the minimal polynomial is of the form (zλ1)(zλm)(z-\lambda_1)\dots (z-\lambda_m)

Proof:

The critical step is TT upper triangular with respect to v1,...,vn    TvkSpan(v1,...,vk)v_1,...,v_n\iff Tv_k\in Span(v_1,...,v_k)

IMportantly, if e1,...,ene_1,...,e_n is the result of Gram-Schmidt, then the Span(v1,...,vk)=Span(e1,...,ek)Span(v_1,...,v_k)=Span(e_1,...,e_k) for all kk.

TvkSpan(e1,...,ek)Tv_k\in Span(e_1,...,e_k) using the same work TekSpan(e1,...,ek)Te_k\in Span(e_1,...,e_k)

Corollary 6.37 (Schur's Theorem)

If VV is finite dimensional complex vector space and TL(V)T\in \mathscr{L}(V), then there exists an orthonormal basis where TT is upper triangular.

Linear Functionals on Inner Product Spaces

Example: φ(R3)=L(R3,R)\varphi\in (\mathbb{R}^3)'=\mathscr{L}(\mathbb{R}^3,\mathbb{R}) given by φ(x,y,z)=2x+3yz\varphi(x,y,z)=2x+3y-z. note φ(V)=v,(2,3,1)\varphi(V)=\langle v,(2,3,-1)\rangle where ,\langle,\rangle is the Euclidean inner product.

Theorem 6.42 (Riesz Representation Theorem)

Suppose that φV=L(V,F)\varphi\in V'=\mathscr{L}(V,\mathbb{F}) on an inner product space VV. Then there exists an unique vector vVv\in V such that φ(u)=u,v\varphi(u)=\langle u, v\rangle

Proof:

Fix an orthonormal basis e1,...,ene_1,...,e_n,

φ(u)=φ(u,e1e1+...u,enen)\varphi(u)=\varphi(\langle u,e_1 \rangle e_1+...\langle u,e_n \rangle e_n)

Use linearity

φ(u)=u,e1φ(e1)+...u,enφ(en)\varphi(u)=\langle u,e_1 \rangle\varphi( e_1)+...\langle u,e_n \rangle \varphi(e_n)

Use the conjugates

φ(u)=u,φ(e1)e1+...u,φ(en)en=u,φ(e1)e1+...φ(en)en\varphi(u)=\langle u,\overline{\varphi( e_1)} e_1 \rangle+...\langle u,\overline{\varphi( e_n)} e_n \rangle=\langle u,\overline{\varphi( e_1)} e_1 +...\overline{\varphi( e_n)} e_n \rangle

Set v=φ(e1)e1+...φ(en)env=\overline{\varphi( e_1)} e_1 +...\overline{\varphi( e_n)} e_n, thus vv exists.

uniqueness v1v2,v1v2=0\langle v_1-v_2,v_1-v_2 \rangle=0 for any v1,v2v_1,v_2 satifsying the conditions.